SPING Block Analgesia in Non-Operative Management of Proximal Femur Fractures in Older Adults Living with Frailty: A Retrospective Cohort Study - Miriam W. A. van der Velden; Thamar Kroes; Nick J. G. Visschers; Frank P. J. F. de Loos; Pleun Janssens; Bart Spaetgens; Miriam C. Faes; Marieke H. J. van den Beuken-van Everdingen; Arnela Suman (Geriatrics)
Background/Objectives: Spinal Phenol IN Glycerol (SPING) block is a novel palliative pain treatment for the non-operative management of proximal femur fractures (PFFs) in older adults living with frailty. Effective pain management that aligns with patient preferences and minimizes opioid use is critical in this setting. This study evaluated the patient, safety, and process outcomes of SPING block in this population. Methods: A retrospective cohort study was conducted in a suburban teaching hospital from March 2021 to June 2024, which included sixty-eight older adults living with frailty that suffered from a PFF and received SPING block. Data were collected from the Electronic Patient Records. The patient living situation was visualized with a Sankey diagram. Changes in pain scores and opioid use were assessed using the Wilcoxon Signed Rank test. Results: The median patient age was 89 years (Interquartile range (IQR) 83–92). Most were severely or terminally ill (American Society of Anesthesiologists (ASA) ≥ 4, 72%) and had cognitive impairment or dementia (68%). SPING block was effective in 93% of patients, significantly reducing median pain scores (4 [IQR 3–5] to 0 [IQR 0–1], p < 0.001) and opioid use (15 mg/day [IQR 4–30] to 0 mg/day [IQR 0–0], p < 0.001). Within 24 h, 84% could sit upright and 44% could transfer between their bed and chair. The median time to discharge was one day (IQR 0–3), with a median survival of 13 days (IQR 7–44). Conclusions: This study supports SPING block as a viable option for older adults living with frailty suffering from a PFF who opt for non-operative management in a palliative setting. SPING block for PFFs in a palliative setting offers effective pain relief, reduces opioid use, and enables mobility for older adults living with frailty. Follow-up is essential to monitor efficacy and safety. Prospective studies are needed to confirm these findings.